2016
DOI: 10.1128/aem.00197-16
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of a Nag-Like Dioxygenase Gene through an Internal Promoter in the 2-Chloronitrobenzene Catabolism Gene Cluster of Pseudomonas stutzeri ZWLR2-1

Abstract: The gene cluster encoding the 2-chloronitrobenzene (2CNB) catabolism pathway in Pseudomonas stutzeri ZWLR2-1 is a patchwork assembly of a Nag-like dioxygenase (dioxygenase belonging to the naphthalene dioxygenase NagAaAbAcAd family from Ralstonia sp. strain U2) gene cluster and a chlorocatechol catabolism cluster. However, the transcriptional regulator gene usually present in the Nag-like dioxygenase gene cluster is missing, leaving it unclear how this cluster is expressed. The pattern of expression of the 2CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Transcription of opaB might be driven by a constitutive promoter located in the internal region of the opa operon. A similar case has been reported for the 2-chloronitrobenzene degradation gene cluster of P. stutzeri ZWLR2-1 32 . There, the internal promoter enhances gene expression to optimize the degradation of 2-chloronitrobenzene.…”
Section: Discussionsupporting
confidence: 82%
“…Transcription of opaB might be driven by a constitutive promoter located in the internal region of the opa operon. A similar case has been reported for the 2-chloronitrobenzene degradation gene cluster of P. stutzeri ZWLR2-1 32 . There, the internal promoter enhances gene expression to optimize the degradation of 2-chloronitrobenzene.…”
Section: Discussionsupporting
confidence: 82%
“…Generally, the enzymes involved in the degradation of chlorinated nitroaromatic compounds were either inducible (Min et al 2014 , 2016 ) or constitutive (Gao et al 2016 ). In this study, whole-cell biotransformation showed that the un-induced strain CNP-8 exhibited negligible activity for 2C4NP.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of xenobiotics is usually activated by transcriptional regulators in the presence of the substrate or its catabolic intermediates (37,38). However, the constitutive expression of degradation-related genes is also found in some strains (35,39). Phenazine-1-carboxylic acid is a microbial antibiotic that is mainly produced by Pseudomonas spp., especially rhizosphere Pseudomonas species (5).…”
Section: Discussionmentioning
confidence: 99%